mFOLFOX6 versus mFOLFOX6 + aflibercept as neoadjuvant treatment in MRI-defined T3-rectal cancer: a randomized phase-II-trial of the German Rectal Cancer Study Group (CAO/ARO/AIO 0214) - Hofheinz, R. D.; Herrle, F.; Dechow, T.; von Weikersthal, L. F.; Welslau, M.; Lettmaier, Sebastian; Burkart, C.; Kubicka, S.; Kochen, L.; Merx, K.; Krause, K.; Ebert, M.; et al. (ESMO Open, 2024)
Background: Neoadjuvant chemotherapy is an option for patients with locally advanced rectal cancer at low risk for local recurrence. This randomized phase II trial investigated whether the addition of aflibercept to modified FOLFOX6 (mFOLFOX6) could improve the rates of centrally confirmed pathological complete remissions (pCR) and (disease-free) survival in magnetic resonance imaging (MRI)-staged cT3 rectal cancer. Patients and methods: Patients with rectal cancer fulfilling the following criteria were included: lower border of tumor >5 cm and <16 cm from anal verge; circumferential resection margin >2 mm and T3-tumor with a maximum infiltration of 10 mm, as determined by MRI. Patients were randomized 1 : 2 to six cycles mFOLFOX6 ± aflibercept. Surgery was scheduled 4 weeks after chemotherapy. Primary endpoint was the rate of centrally confirmed pCR. The study was designed to detect an improvement of pCR from 10% to 27% (power 80%, type I error 20%). Results: A total of 119 randomized patients started treatment (39 patients mFOLFOX6, arm A, and 80 mFOLFOX + aflibercept, arm B). The incidence of all grade adverse events was similar in both arms, however, adverse events grade ≥3 were more than twice as high in the experimental arm due to hypertension. Surgical complications were comparable. Aflibercept did not improve the pCR rate (arm A 26% versus arm B 19%, P = 0.47) and more patients in arm B had node positivity. With a median follow-up of 40.1 months, the 4-year disease-free survival was 83% in arm A and 85% in arm B (P = 0.82). Only two patients in arm A and one patient in arm B developed local recurrence. Conclusions: In patients with locally advanced rectal cancer and MRI-defined low risk of local recurrence, neoadjuvant mFOLFOX6 + aflibercept was feasible and did not compromise surgery. Survival data were favorable in both arms, but pCR rates were not increased by the addition of aflibercept.
CRIS-Team Scopus Importer:2024-09-20
Keywords: aflibercept; neoadjuvant chemotherapy; rectal cancer